Análise da atenção domiciliar prestada pelas Equipes de Atenção Primária a Saúde em Minas Gerais de 2010 a 2015 - Leandro Martins Diniz (2018)
Analysis of home care provided by the primary health care teams in Minas Gerais, 2010 to 2015. Home care (HC) is a modality of health care that is expanding in Brazil and in the world. Public and private services have invested in the implementation of this type of assistance, due to its potential to transform the current model of care, highlighting the work of the Primary Health Care (PHC) teams. Given the importance of knowing the scenario of distribution of these services in the territories, as well as outlining the work profile of AD professionals, it is justified to carry out this study. The objective was to analyze the number of home visits (HV) carried out under the PHC, in the Unified Health System (SUS) in Minas Gerais (MG), according to the professional categories, from 2010 to 2015. Other objectives were to compare the rates (RT) among health macro-regions and determine their spatial distribution. This is an ecologically based epidemiological study with a quantitative approach. The amount of HV performed in the period from 2010 to 2015, by the professional categories that make up the SUS PHC teams (mid-level professionals, nurses, physicians and other professionals of higher education) were collected in the Basic Attention Information System. The RT calculation weighted the population size of the municipality and used as reference the average number of people in the area covered by the PHC teams (3,000 inhabitants). Descriptive and inferential analyzes (Mann-Whitney test) estimated and compared the medians of the RT of HV among the professional categories and between the macro-regions of health, for each year separately, with the software InStat 3.0. The spatial distribution of the RT of HV was verified by plotting maps in ArcGIS® software 10.4.1. Significant differences (p <0.05) in RT of HV were identified between professional categories and between macro regions. Higher values were found for mid-level professionals in relation to nurses, physicians and other higher level professionals. The median of the RT of HV in 2010 of high school professionals was 515.0, followed by 258.7 of the nurses, 112.2 of the physicians and 62.4 of the other professionals of higher level. The Southeastern, Southern, South Eastern and Southern Triangle macro-regions performed better in AD actions than the Center macro-region. It is concluded that the HV profile performed in SUS in MG has a high quantitative, but unevenly distributed among professional categories and macro-regions of health. It is essential that the services are aware of the general landscape of HC in the territories of the PHC teams, so that it is possible to reduce regional inequities and minimize discrepancies between professionals, in view of the qualification of the care provided, through the improvement of PHC.